Clothes in hot and cold places - "Crisp Simon" (Wayland Hove, 1994)
The book Clothes in Hot and Cold Places by Simon Crisp, published in 1994 by Hodder Wayland. This 32-page hardcover is part of the "Hot & Cold Places" series and examines the clothing and accessories worn by people in various climates around the world. The book is illustrated with color photographs and artwork throughout, providing a visual understanding of how climate and available materials influence clothing styles.